Pengembangan E-Modul IPA Berbasis Question Prompt Scaffolding Tema Tekanan Hara Pada Si Hijau Untuk Menumbuhkan Kemampuan Argumentasi Siswa Kelas VIII - NURGHAISANI FAHRANA, DINI; BERLIAN, LISKA; ZAKY EL ISLAMI, R. AHMAD (PendIPA Journal of Science Education, 2025)
The ability to argue well is one of the important requirements in science learning. However, learning that aims to develop students' argumentation skills has not been implemented properly. One solution is to provide learning materials that contain indicators of argumentation skills. These indicators will be presented in the form of an E-Module based on Question Prompt Scaffolding. The purpose of this research and development was to test the validity and readability of the E-Module. This E-Module focuses on the theme of Nutrient Pressure on Green Plants with the aim of improving the argumentation skills of eighth-grade students. The research method used is Research and Development (R&D). The Research and Development (R&D) model is based on the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Various instruments were used in this study, including a validation questionnaire evaluated by three experts. These experts included subject matter experts, media experts, and science teachers. Additionally, a readability questionnaire was used to measure the readability of the E-Module. The validation results showed that the E-Module achieved an average score of 86% and fell into the “Highly Valid” category. This assessment was based on the subject matter expert's score of 82%, the media expert's score of 91%, and the science teacher's score of 86%. The readability of the E-Module was determined based on students' responses and achieved a score of 94%, categorized as “Very Good.” This proves that the Science E-Module based on Question Prompt Scaffolding with the theme of Nutrient Pressure on Green Plants is considered valid by all validators.